Integration Processes in European R&D: A comparative spatial interaction approach using project based R&D networks, co-publication networks and co-patent networks - Rafael Lata; Thomas Scherngell; Thomas Brenner (European Regional Science Association (ERSA), 2012)
The focus of this study is on integration processes in European R&D by analyzing the spatio-temporal dimension of three different R&D collaboration networks across Europe. These networks cover different types of knowledge creation, namely co-patent networks, project based R&D networks within the EU Framework Programmes (FPs) and co-publication networks. Integration in European R&D – one of the main pillars of the EU Science Technology and Innovation (STI) policy – refers to the harmonization of fragmented national research systems across Europe and to the free movement of knowledge and researchers. The objective of this study is to describe and compare spatio-temporal patterns of the observed networks at a regional level, and to estimate the evolution of separation effects over the time period 1999-2006 that influence the probability of cross-region collaborations in the distinct networks under consideration. By separation effects we refer to geographical, technological, institutional and cultural barriers between the regions under consideration. The study adopts a spatial interaction modeling perspective, econometrically specifying a panel generalized linear model relationship taking into account spatial autocorrelation among flows by using Eigenfunction spatial filtering methods to address the research questions. The European coverage is achieved by using 255 NUTS-2 regions of the 25 pre-2007 EU member-states, as well as Norway and Switzerland. For the construction of the three dependent variables that describe collaboration intensities between all region pairs in the three different types of R&D networks, we use data from the OECD Regpat database to capture cross-region co-patent networks, the AIT EUPRO database to capture cross-region project based R&D networks in the FPs, and the Scopus database to capture cross-region co-publication networks. The independent variables consist of one origin measure, one destination measure and seven separation measures. The separation variables focus on barriers that may hamper cross-region collaboration probability, accounting for spatial effects, cultural and institutional hurdles and economic or technological barriers. The results will provide novel and valuable empirical insight into ongoing integration processes in different types of R&D, reflecting knowledge diffusion in form of R&D collaborations from a longitudinal and comparative perspective. By this, the study will produce important implications regarding past success or failure of European R&D integration policies, and, thus, for future STI policy design.
Keywords: C23; O38; L14; R15; 330; R&D Networks; European Framework Program; Patents; Publications; Large-Scale Networks; Spatial Interaction Modelling; Panel Econometrics; Eigenvector Spatial Filtering; Social Network Analysis